Characterizing the Effect of the Lysine Deacetylation Modification on Enzyme Activity of Pyruvate Kinase I and Pathogenicity of Vibrio alginolyticus - Xu, Zhou; Wang, Linjing; Wang, Xudong; Wan, Mingyue; Tang, Mei; Ding, Yu (Frontiers in Veterinary Science, 2022)
Pyruvate kinase I (PykF) is one of the key enzymes of glycolysis and plays a crucial role in bacterial metabolism. Several acetylation sites of Vibrio alginolyticus PykF were reported in previous studies and then 11 sites were first verified in this study, however, the specific roles of PykF acetylation remains unclear. Overlap-PCR and homologous recombination were implied to delete V. alginolyticus pykF gene and constructed complementary strains of site-directed mutagenesis for the further research focus on the deacetylation regulation on PykF. The results showed that the pyruvate kinase activity was sharply suppressed in the deacetylation status of K52, K68, and K317 of PykF, as well as the extracellular protease activity was significantly decreased in the deacetylation status of K52 and K68, but not induced with K317. Moreover, the growth rates of V. alginolyticus were not influenced with these three deacetylation sites. The ΔpykF mutant exhibited a 6-fold reduction in virulence to zebrafish. Site-directed mutations of K52R and K68R also showed reduced virulence while mutations of K317R didn’t. The in vitro experiments showed that PykF was acetylated by acetyl phosphate (AcP), with the increase of incubation time by AcP, the acetylation level of PykF increased while the enzyme activity of PykF decreased correspondingly. Besides, PykF was deacetylated by CobB deacetylase and in result that the deacetylation was significantly down-regulated while the pyruvate kinase activity of PykF increased. Moreover, deletion of cobB gene had no significant difference in pyruvate kinase activity. These results confirm that CobB can regulate the acetylation level and pyruvate kinase activity of PykF. In summary, the results of this study provide a theoretical basis for further understanding of the deacetylation modification of PykF. It provides a new idea for the prevention and cure of vibriosis.